Implementasi Metode Project-Based Learning berbantuan Video Pembelajaran pada Mata Pelajaran Instalasi Motor Listrik - Nabil, Muhammad; Hendri, Hendri (Jurnal Pendidikan Teknik Elektro, 2025)
Students in Vocational High Schools have low learning motivation when carrying out learning activities. This can happen because the way the material is delivered and the way the learning evaluation is carried out by the teacher tends to be monotonous and less creative so students feel bored, lazy, and less interested during the learning process. This causes student learning outcomes to be low. In the subject of Electric Motor Installation, there are many explanations of the material that are a little complicated for students to understand. Implementing the assistance of learning videos in the Project-Based Learning learning model, is considered quite effective in rekindling the enthusiasm for learning possessed by students. The objective to be achieved in this study is to find out the impact of implementing the Project-Based Learning model with the help of learning videos on the subject of Electric Motor Installation. The type of research used in this study is experimental research with a pre-experimental design type with a special design form, namely one group pretest-posttest. This research design is used to measure changes in students' understanding or learning outcomes before and after the application of the Project-Based Learning method assisted by learning videos. Based on the research that has been done, it was found that the application of the Project-Based Learning method assisted by learning videos has a positive impact on students' understanding and learning outcomes during the learning process in the Electric Motor Installation subject.